2014
DOI: 10.1093/infdis/jiu202
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus in Adolescent Girls Before Reported Sexual Debut

Abstract: Background. Human papillomavirus (HPV) vaccines are recommended for girls prior to sexual debut because they are most effective if administered before girls acquire HPV. Little research has been done on HPV prevalence in girls who report not having passed sexual debut in high HPV-prevalence countries.Methods. Using attendance registers of randomly selected primary schools in the Mwanza region of Tanzania, we enrolled girls aged 15–16 years who reported not having passed sexual debut. A face-to-face interview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“… 11 Girls were enrolled between January and August 2012, and followed 3-monthly for 18 months. At each visit, girls had a face-to-face interview in Swahili with a female study nurse using a structured paper questionnaire, 11 and one nurse-assisted, self-administered vaginal Dacron swab was obtained, irrespective of reported sex. Girls who reported previous sex were offered a pregnancy test and asked about symptoms of reproductive tract infections at every visit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Girls were enrolled between January and August 2012, and followed 3-monthly for 18 months. At each visit, girls had a face-to-face interview in Swahili with a female study nurse using a structured paper questionnaire, 11 and one nurse-assisted, self-administered vaginal Dacron swab was obtained, irrespective of reported sex. Girls who reported previous sex were offered a pregnancy test and asked about symptoms of reproductive tract infections at every visit.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Methods for DNA extraction, amplification and genotype detection were described previously. 11 Specimens negative for β-globin amplification were excluded, since vaginal sampling was assumed to be unsuccessful. …”
Section: Methodsmentioning
confidence: 99%
“…These routes likely account for a very small proportion of acquisition. In a cohort of schoolgirls resident in Tanzania, who reported not having passed sexual debut, HR-HPV genotypes were detected in 5.3% of self-administered vaginal swabs [81]. An underreporting of sexual activity may account for this finding, as may the practice of intra-vaginal cleansing, an activity common in East Africa.…”
Section: The Role Of Hpv In Ano-genital Cancersmentioning
confidence: 99%
“…[9,10] The few published studies on HPV infection in adolescent girls in SSA suggest that HPV prevalence may be very high at a young age. A study in Tanzania found HPV prevalences of 73% in sexually active girls aged 14-18 years, and one in Uganda in girls aged [12][13][14][15][16][17][18][19][20][21][22][23][24] found a prevalence of 75%. [11,12] A recent study in Tanzanian girls aged 15-16 years who reported no previous penetrative sex found an HPV prevalence of 8%.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] A recent study in Tanzanian girls aged 15-16 years who reported no previous penetrative sex found an HPV prevalence of 8%. [13] The prevalence of non-optimal vaginal microbiota, including bacterial vaginosis (BV), is particularly high in SSA. [14] The vaginal microbiome may modulate susceptibility to HPV infection, as well as other sexually transmitted infections (STI) and HIV.…”
Section: Introductionmentioning
confidence: 99%